LIFESTYLE AND PRICE PERCEPTION EFFECTS ON YOUTH THRIFTING PURCHASE DECISIONS AT L21 SHOP, CIREBON - Chaterin Aulia Virginia; Bambang Sumardi; Winda Dwi Yanthi (PT. Berkah Digital Teknologi, 2025)
Purpose: To examine the effects of lifestyle and price perception on youth purchase decisions for imported second-hand clothing (thrifting) at L21 Shop, Cirebon Regency, Indonesia. Research Methodology: Quantitative survey; purposive sampling; 100 respondents aged 16–30 who have purchased from L21 Shop; questionnaire; data analysis using SPSS with descriptive statistics, classical assumption tests (Kolmogorov-Smirnov normality), and multiple linear regression. Results: Lifestyle and price perception show significant positive effects on purchase decisions, both individually and jointly. Limitations: Single-store, cross-sectional design with non-probability sampling and self-reported measures may limit generalizability. Contribution: Provides evidence for thrift retail marketing and consumer behavior studies; offers practical guidance for SME thrift stores to align product selection and pricing with youth lifestyle trends.